Proliferating ameloblastomatous calcifying odontogenic cyst: A rare case report - Monika Negi; Abhiney Puri; Rajat Nangia; Namita Sepolia (Wolters Kluwer Medknow Publications, 2020)
Calcifying odontogenic cyst (COC) has many traits of an odontogenic tumor and has in veracity been categorized as such in the World Health Organization publication histologic typing of odontogenic tumors. COC is an unconventional developmental odontogenic cyst first recited by Gorlin in 1962. It is a rare pathology and accounts for only 1%-2% of jaw cyst reported. There has always been a question whether its a cyst, neoplasm, or hematoma. Ameloblastoma is one of the well-known odontogenic tumors that can be conglomerated with COC but only a few reports include subjective clinical and radiographic features. Here, we present a specified case report of the COC with ameloblastic proliferation which is an exceptionally rare histologic variant. The classical histological features of lining epithelium and characteristic ghost cells are seen sideways with ameloblastomatous proliferations. The case is ventilated here because of its singularity.